PENGARUH CONTEXTUAL TEACHING AND LEARNING (CTL) MELALUI MEDIA FLIPCHART TERHADAP PENGETAHUAN KONSEPTUAL SISWA PADA MATERIORGANISASI KEHIDUPAN KELAS VII SMP METHODIST PEKANBARU T.A 2015/2016 - Martala Sari (Lectura: Jurnal Pendidikan, 2017)
The purpose of this research was to know the effect of contextual teaching ang learning (CTL) trough flipchart on student’s concept knowledgeof the subject maters biological organization. This research conducted on November-December 2015 at class VII SMP Methodist Pekanbaru. The design used in this research was quasi experimental research of nonequivalent pretest-posttest control group design. The subjects of this research were student of VIIaand VIIb in which each class consisted of 26 students selected by total sampling technique. Data were collected through pretest, posttest, and observation sheet. The data was alwaysed by using t-test. It showed that the average of N-Gain at experiment class was 0,55 categorized into medium level, while at control class was 0,22 categorized into low level. Derived from t-test, it also showed that significant difference in student’s concept knowledge between control and experiment class. Overall, it can be concluded that Contextual Teaching and Learning (CTL) through flipchart had significant difference in student’s concept knowledge of the subject maters biological organization in class VII SMP Methodist Pekanbaru academic year 2015/2016. Keywords: contextual teaching and learning, concept knowledge, filipchart, biological organization